Application of a Susceptible, Infectious, and/or Recovered (SIR) Model to the COVID-19 Pandemic in Ecuador - Espinosa, Pablo; Quirola‐Amores, Paulina; Teran, Enrique (Frontiers in Applied Mathematics and Statistics, 2020)
The coronavirus disease 2019 (COVID-19) pandemic is wreaking havoc in healthcare systems worldwide. COVID-19 was reported for the first time in Wuhan (China) and the first case in Ecuador was confirmed on 27 February 2020. Several determinants are taken into consideration for establishment of asymptomatic or critical illness, and are necessary to predict the dynamics and behavior of a pandemic. We generated a Susceptible, Infectious, and/or Recovered (SIR) model and reflected upon the COVID-19 pandemic in Ecuador. For the entire Ecuadorian population, we estimated that the reproduction number (R0) was 2.2, with 88% susceptible/infected individuals. To stop a national epidemic, a quarantine for 3–4 months is required, and when 55% of the population has been immunized (equivalent to 110 days since the first report of a COVID-19 case), a real decrease of new cases will be observed. The effectiveness of quarantine should be analyzed retrospectively, and not as a result of contemporary control of the COVID-19 epidemic.